Reasons for non-response to a direct-mailed FIT kit program: lessons learned from a pragmatic colorectal-cancer screening study in a federally sponsored health center. Issue 1 (4th September 2014) - Coronado, Gloria D; Schneider, Jennifer L; Sanchez, Jennifer J; Petrik, Amanda F; Green, Beverly
Abstract: Colorectal cancer screening rates are below optimal. As part of a pilot clinic-based pragmatic study aiming to raise rates of colorectal-cancer screening, we explored patients' reasons for not responding to a direct-mailed screening invitation. We conducted telephone interviews with patients who were mailed a fecal immunochemical test (FIT) but who did not return it to the lab. Interviews were audio-recorded, transcribed, and coded for thematic analysis. We met our goal of 20 interviews (10 in English and 10 Spanish; 75 % female). Reasons for not completing tests were fear of results or cost of follow-up colonoscopy ( n  = 9); not having received the test in the mail ( n  = 7); concerns about mailing fecal matter or that test results could be mixed up ( n  = 6); and being busy or forgetful ( n  = 4). Efforts to improve uptake of colorectal cancer screening in a direct-mailed program ought to address concerns identified in our study.